Validity and Reliability Analysis Using the Rasch Model to Measure the Quality of Mathematics Test Items of Vocational High Schools - Adi, Nur Romdlon Maslahul; Amaruddin, Hidar; Adi, Habib Maulana Maslahul; A'yun, Isna Laili Qurroti (Universitas Negeri Semarang, 2022)
Teachers are expected to be able to evaluate the learning process and also be able to develop evaluation tools or instruments used in the learning process. Test items are considered appropriate if they are valid and able to measure the level of suitability and reliability or consistency. The purpose of this study was to analyze the quality of the test items and the mathematical ability of the XII grade students of the State Vocational School in one of State Vocational School in Semarang District. This research is a quantitative descriptive study that describes the quality of the mathematics test items made by the teacher and the students' abilities in mathematics. The subjects in this study were 126 student response patterns to the test instrument in the form of multiple choice questions totaling 20 items for class XII students. Rasch model was used to analyze this research with the help of Winsteps 3.73 software. A total of 20 items were tested, there was only one item, namely item number 7, which did not fit, which means it does not function normally to measure students' abilities. The ability of students who are relatively weak with Person Reliability of 0.48. The results showed that the quality of the test items was applicable. This is indicated by the Item Reliability value of 0.95 which means that the items are very good for evaluating students' abilities.